Chandler's Three Faces of Capitalism - Nelles, H. V. (Labour / Le Travail, 1991)
The article reviews and comments on the book, "The Dynamics of Industrial Capitalism," by Alfred D. Chandler, Jr.
Keywords: BOOKS -- Reviews; CHANDLER, Alfred D. (Alfred Dupont), 1918-2007; Capitalism; DYNAMICS of Industrial Capitalism, The (Book); Nonfiction